Selective Sequential Zero-Base Budgeting Procedures Based on Total Factor Productivity Indicators - Ishikawa, A.; Sudit, E. F. (Management Science, 1981)
The authors' purpose in this paper is to develop productivity-based sequential budgeting procedures designed to expedite identification of major problem areas in bugetary performance, as well as to reduce the costs associated with comprehensive zero-base analyses. The concept of total factor productivity is reviewed and its relations to ordinary and zero-based budgeting are discussed in detail. An outline for a selective sequential analysis based on monitoring of three key indicators of (a) implicitly budgeted total factor productivity; (b) revenue growth; and (c) profitability; is suggested. It is argued that this approach is instrumental in promoting a more systematic performance analysis, which is capable of revealing hidden efficiency shortfalls and is potentially cost and time saving. Additionally, this type of productivity-based budgeting is shown (via use of an actual application) to provide all the informational inputs for a full-fledged analysis of expected budgetary distribution of productivity gains among various categories of employees, shareholders and customers.